1995
DOI: 10.1055/s-0038-1649882
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometric Detection of Activated Platelets in Pregnant Women Prior to the Development of Pre-Eclampsia

Abstract: SummaryPre-eclampsia is a common complication of pregnancy, in which platelets may have an early pathogenetic role. In this prospective study a whole blood flow cytometric method has been used to detect circulating activated platelets in pregnant women prior to the development of pre-eclampsia. Activated platelets were identified by bound fibrinogen or by CD63 antigen expression. Of 121 healthy primiparous women studied at 28 weeks of pregnancy, 18 (15%) developed clinical pre-eclampsia six to thirteen weeks l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0
7

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(73 citation statements)
references
References 19 publications
5
61
0
7
Order By: Relevance
“…As a result, the phenotype of decidual leukocytes might be different in preeclampsia, a possibility we are currently examining. Preeclamptic cytotrophoblasts also fail to express PECAM-1, raising the additional possibility that they have faulty interactions with platelets, a particularly intriguing possibility because platelet activation is a frequent complication of preeclampsia (35).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the phenotype of decidual leukocytes might be different in preeclampsia, a possibility we are currently examining. Preeclamptic cytotrophoblasts also fail to express PECAM-1, raising the additional possibility that they have faulty interactions with platelets, a particularly intriguing possibility because platelet activation is a frequent complication of preeclampsia (35).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the coagulation cascade, especially alterations in platelet function, can be demonstrated weeks to months before clinically evident disease. 54,55 Similarly, increased sensitivity to angiotensin 46 and reduced plasma volume 56 have been found in groups of women destined to develop PE. It is important to point out that these changes are not universally present and thus can only be recognised in groups of women destined to develop PE.…”
Section: Endothelial Dysfunction In Pre-eclampsiamentioning
confidence: 93%
“…4' 5 An example of flow cytometric detection of platelet activation in preeclarnpsia is the finding by Janes and Goodall 6 of a significantly increased platelet surface expression of CD63, a marker for secretion of platelet lysosomal granules, compared with normotensive pregnancy. In a prospective study Janes et al 7 also found an increased expression of CD63 at 28 weeks' gestation in pregnant women before the development of preeclarnpsia.…”
mentioning
confidence: 87%